PTU-001 Attitudes of uk gastroenterology trainees to research and out of programme experience: results from the 2016 national academic training survey. (17th June 2017) - Bhala, N; China, L; AlRaiby, L; Chedgy, F; Disney, B; Farmer, A; Fogden, E; Sadler, G; Hull, M; McLaughlin, J; Ellison, H; Solomon, J; et al.
Abstract : Introduction: Previous national surveys of United Kingdom gastroenterology trainees (1-2) identified high rates of participation in research and Out Of Programme Experience (OOPE). Although 63% of trainees who have not done so intend of take time OOPE during training, 3 the current state of attitudes to research remains unclear. Method: The aims were to determine: (1). Trainees' experience of OOPE/research; (2). The perceived reasons for and against; and (3). Viewpoints on future career prospects. A Web-based national survey of trainees in Gastroenterology in the United Kingdom was carried out in 2015–16, supported by the BSG Research Committee. Results: 178 trainees completed the survey in 2016, of which 37.6% (n=67) were female. 88.1% (n=155) of trainees were in clinical training programmes, with 11.9% (n=21) in an academic training programme. 64.2% (n=106) had published a recent peer-reviewed journal article. 47.3% (n=78) had recruited patients to Clinical Research Network (CRN) adopted studies and certificate for Good Clinical Practice (GCP) was held by 63.0% (n=104). Of those doing research, trainees reported success rates of around 40% for competitive clinical research fellowships, but these were particularly higher in pump-priming and pre-funded posts (>80%). 84.5% (n=148) of trainees expressed a wish to undertake OOPE/research. The most common reasons for undertaking OOPE were: (i) career prospects (75.2%); (2) academic interests (66.7%); and (iii) educational benefits (66.1%). The most common reasons for not undertaking OOPE were: (i) personal choice (83.2%); (ii) financial costs (69.7%); and (iii) family commitments (65.4%). 93.6% (n=161) of trainees feel that a higher degree will make them more competitive at consultant interviews. 88.9% feel that OOPE/research will continue to be important and 91.1% feel that developing regional trainee networks are important. Conclusion: The majority of gastroenterology trainees who responded express a desire to undertake OOPE and rates of participation in research/OOPE remain high. Efforts to do so include presentations, publications, GCP, hands-on research via CRN and regional networks (which many are interested in helping with). Despite smaller absolute numbers responding, gastroenterology trainees appear to be competitive for fellowships, especially if pump-primed. Efforts need to be made to tackle barriers to do OOPE/research but most trainees surveyed were positive about career and academic benefits including help in securing future consultant posts. Reference: . Fogden EN, et al. Gut2009;58(Suppl I):A155 2. Disney B, et al. Gut 2011;60(Suppl I):A119. 3. BSG Trainees: 2014– Executive Summary Disclosure of Interest: None Declared